Histological features of the placenta and their relation to the gross and data from Thoroughbred mares - Pazinato, Fernanda M.; Curcio, Bruna R.; Fernandes, Cristina G.; Feijó, Lorena S.; Schmith, Rubia A. [UNESP]; Nogueira, Carlos E.W. (FapUNIFESP (SciELO), 2016)
The placenta is a transitory organ that originates from maternal and fetal tissues, the function of which is transporting nutrients from the mother to the fetus. The aim of this study was describe the histological features of placentas in healthy Thoroughbred mares at foaling and evaluate their relation with the gross placental and data of these mares. For this study 188 Thoroughbred mares were used. It was performed clinical observation for signs of placentitis during daily health checks and ultrasonic examination monthly to assess the fetus and placenta. All of the mares that exhibited clinical signs of placentitis were treated during gestation. The parturition was assisted, the placentas were grossly evaluated and samples were collected immediately after expulsion. The following data were considered for each mare: age, gestational age, number of parturition, time for placental expulsion, umbilical-cord length, placental weight and clinical signs of placentitis. Histological evaluation of the placentas revealed extensive cytoplasmic vacuolization of the epithelial areolar cells, presence of inflammatory infiltrates and hypoplasia-atrophy of the microcotyledons. Most of the gross placental findings were consistent with the histological results. In conclusion the mares with a vacuolated placental chorionic epithelium were older and had experienced a larger number of births. Great part of the mares with inflammatory infiltrates did not showed any clinical signs of placentitis during gestation.
Keywords: Histology; Infiltrates; Placenta; Thoroughbred mares; Vacuolization